Malnutrition upon Hospital Admission in Geriatric Patients: Why Assess It? - Orlandoni, Paolo; Venturini, Claudia; Jukic Peladic, Nikolina; Costantini, Annarita; Di Rosa, Mirko; Cola, Claudia; Giorgini, Natascia; Basile, Redenta; Fagnani, Donata; Sparvoli, Debora; David, Serenella (Frontiers in Nutrition, 2017)
Abstract Objective To assess the prevalence of malnutrition according to the new ESPEN definition in a population of geriatric hospital patients and to determine how malnutrition affects the length of hospital stay and hospital mortality. Design A retrospective analysis of data gathered during nutritional screening surveys carried out three consecutive years, from 2012 to 2014, in an Italian geriatric research hospital (INRCA, Ancona) was performed. On the day of the study, demographic data, data on clinical conditions and the nutritional status of newly admitted patients were collected. Patients were screened for malnutrition risk using the Malnutrition Universal Screening Tool. Subsequently, malnutrition was diagnosed, for subjects at high risk, following the criteria suggested by the European Association for Clinical Nutrition and Metabolism (BMI < 18.5 kg/m2 or different combinations of unintentional weight loss over time and BMI values). Sensitivity, specificity, positive and negative predictive value of MUST tool compared to ESPEN criteria, were assessed. The characteristics of patients with a diagnosis of malnutrition were compared to those of non-malnourished patients. The impact of malnutrition on length of hospital stay and hospital mortality was investigated through logistic and linear regression models. Setting The study was performed in an Italian geriatric research hospital (INRCA, Ancona). Subjects Two hundred eighty-four newly hospitalized geriatric patients from acute care wards (mean age 82.8 ± 8.7 years), who gave their written consent to participate in the study, were enrolled. Results According to the Malnutrition Universal Screening Tool, high risk of malnutrition at hospitalization was found in 28.2% of patients. Malnutrition was diagnosed in 24.6% of subjects. The malnutrition was an independent predictor of both the length of hospital stay and hospital mortality. The multivariate analyses - linear and logistic regression - were performed considering different potential confounders contemporarily. The results showed that the malnutrition is an independent predictor of length of hospital stay and hospital mortality. Malnourished subjects were hospitalized almost 3 days longer compared to non-malnourished patients (p=0.047; C.I. 0.04 - 5.80). The risk of death during hospitalization was 55% higher for malnourished patients (p=0.037; C.I. 0.21 - 0.95). Conclusions A new ESPEN consensus of malnutrition